SISTEM INFORMASI BOOKING LAPANGAN FUTSAL BERBASIS WEB DENGAN FITUR FIND MATCH - Triansyah, Rizkie; Juanito, Sebastian Fajar; Mendrofa, Malfin; Ismawati, Nur (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
In the present technology is developing very quickly, technology is very helpful for human work, from the ease of transacting, getting information, and so on. In this digital age, sports are very important activities, sports are very fun activities for most people, such as Futsal. It's just that to play futsal requires a special field, while to play on the futsal field, in some places futsal is required to make a booking because of the tight schedule, and the problem is when the customer comes to the location with a considerable distance and it turns out that the futsal place is full booked it is an unpleasant thing for the customers. Here we try to solve the problem by creating an online booking application futsal field via the web, which certainly helps customers to make reservations and scheduling the field regularly and surely. This research aims to explain and describe the booking applications in Futsal 4D by building the results of the booking application design using PHP & MySQL programming grammar. The benefit of this research is to provide a positive outlook for Futsal 4D customers regarding easy, effective, and efficient booking applications and Futsal 4D customers feel more helped by this application.